Vacant wall, versatile screen, and personal gateway: design implications for the impact of smartphone use on the domestic spaces of single-person student households. Issue 1 (2nd January 2023) - Kim, Hoyoung
ABSTRACT: Recently, there has been a phenomenon wherein smartphones have begun to serve as substitutes for televisions in domestic spaces. However, there have been few studies of investigating the relationship between smartphone use and domestic spaces. To obtain a deeper understanding, this study intends to investigate how smartphone use has influenced the behaviors of residents within their domestic spaces. In particular, this study first aims to examine the interrelation between smartphone use and the domestic spaces of single-person student households. To this end, this study conducted on-line surveys and semi-structured interviews based on non-probability purposive sampling. The research participants were asked about their media technology use and the behavioral characteristics of their single-person households, the differences in their preferences between watching television and using their smartphones, and relationships between smartphone use and the physical environment of single-person households. The findings of this study suggest that participants often lose interest in the vertical walls of their domestic spaces due to the postures they maintain while using smartphones. Instead of paying attention to vertical walls, smartphone screens have become versatile places wherein people can communicate with others and enjoy leisure activities. Based on these findings, this study proposes three design suggestions.